(untitled) (Research, Society and Development, 2025)
This article aims to analyze the differences, advantages, challenges, and synergies between additive and subtractive manufacturing processes in the context of Industry 4.0. The adopted methodology was a bibliographic review, considering publications from the last five years on the topic. The results indicate that while additive manufacturing stands out for its design flexibility and waste reduction, subtractive manufacturing offers greater dimensional accuracy and mechanical strength. The integration of these technologies into hybrid systems has proven to be a promising solution for cost optimization and production efficiency. The conclusion highlights the need for investment in research to overcome economic and technical challenges, promoting broader adoption of these technologies in the industry.